HOUSEHOLD STRUCTURE AND STUDENTS’ ACADEMIC PERFORMANCE: A COMPARATIVE ANALYSIS OF CHILDREN RAISED BY GRANDPARENTS AND SINGLE PARENTAGE - Oyetakin Sylvia Olayemi (European Scientific Journal, ESJ, 2014)
The dissertation examined house hold structure and students academic performance with a major focus on the comparative analysis of children raised by grandparents and single parentage in Lagos State senior Secondary schools. The general awareness of the importance of the home environment on student’s academic performance necessitate an investigation into the family structure as it affects the students’ academic outcome. The research design was a fusion of questionnaire technique with field observation and oral interview. The population for this study consisted of all the students, and teachers in the senior secondary schools in addition to market women in selected markets in Ojo local Government area of Lagos State. Based on this, ten (10) senior secondary schools were purposefully sampled comprising of ten 10 students from separate single parents home and ten (10) students raised by their grandparents, a total of two hundred students. Also, fifty (50) teachers and ten 10 market women were sampled. Three research questions and three hypotheses were advanced and tested in the study. Three types of questionnaires were used, titled questionnaire on parenthood for students (QPS), questionnaire on parenthood for teachers (QPT), and questionnaire for market women (QPMW). These instruments were validated and found reliable at r=0.88. The study revealed that no significant difference existed between the academic performance of students from single parents and those from two parent families (t cal.2760.05). However, significant difference existed in the means of the academic performance of male students from single parent and male students from two parent family (df=(3,28), 83.74, p<0.05) and female students from single parent and female students from two parent families. Also, there is difference between the academic performance students raised by grandparents and students from single parent families (df=(3,28), 31.54, p<.05). From the findings and conclusion of this study, sufficient evidence were provided such as government initiating educative and enlightenment programme on how to improve and sustain intact parenthood through the mass media and that fund to the assistance of victims of single parenthood.